Changing composition of private investment in Indian agriculture and its relationship with public investment and input subsidies - Kumar, Anjani; Bathla, Seema; Verma, Smriti (International Food Policy Research Institute, 2020)
Using the decennial All-India Debt and Investment Survey from 1981-82 to 2012-13, this paper delves into the spatial and temporal trends in private fixed capital expenditure and its composition, among rural households in India. We also assess its relationship with public investment in agriculture. Amidst sizeable ups and downs, the magnitude and rate of growth in private investment in agriculture has gained momentum from 2000s except in Odisha, Himachal Pradesh, Jammu and Kashmir. An increasing preference of farmers to invest in residential land and buildings, and that at the cost of asset formation in farm business, is evident in agriculturally advanced states. Within agriculture, relatively higher investments in land improvement, machinery-implements, tractors, and livestock are identified over the period. Importantly, such investments are positively influenced by public investments in agriculture and irrigation in the high and low income states and also by public spending on input subsidy in the middle and low income states. An increase in public expenditure that is well targeted and is commensurate with farmers’ investment portfolio would reinforce a complementary relation between the two across-the-board. The impact of terms of trade on private investment though positive turns out to be statistically insignificant. Land acts as a constraint, indicating need for policy interventions that augment crop yield and can bring remunerative prices to farmers. A continued effort to improve the outreach of formal financial institutions for credit is warranted for higher private capital formation.